2021
DOI: 10.31462/jcemi.2021.01012021
|View full text |Cite
|
Sign up to set email alerts
|

Safety net applications in developing countries: Turkey and Iran case study

Abstract: In this study, safety net applications, which are used as a collective protection measure in high-rise building constructions, in small and medium sized enterprises were investigated. For this purpose, safety net inspection form has implemented to building construction sites in Turkey and Iran. Study is focused on not only the presence of safety measures, but also the importance of correct application. In addition, it is aimed to draw attention to both the failures in the safety net applications and the genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The research shows that under the impact of nominal protection energy level, E M of flexible protection system is far less than E I , which can ignore in design [21] E I is contributed by the deformation of the energy dissipator, intercepting net, suspended frame, and wire ropes. The deformation of the suspended frame and the wire rope should stay in the elastic stage to ensure the safety of the system, so the energy consumption of these two parts can disregard.…”
Section: Design Methods 41 Energy Matchingmentioning
confidence: 97%
See 1 more Smart Citation
“…The research shows that under the impact of nominal protection energy level, E M of flexible protection system is far less than E I , which can ignore in design [21] E I is contributed by the deformation of the energy dissipator, intercepting net, suspended frame, and wire ropes. The deformation of the suspended frame and the wire rope should stay in the elastic stage to ensure the safety of the system, so the energy consumption of these two parts can disregard.…”
Section: Design Methods 41 Energy Matchingmentioning
confidence: 97%
“…Among those, protective nets are used more frequently because of the large area protection characteristics. Çelik [21] studied the application of protective nets in engineering and provided evaluations and suggestions for the shortcomings in the application. Filho [22] compared two fall protection measures used in construction in Brazil and found that protective measures with safety nets are safer.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Mhando [33] mentions that inefficient use of personal protective equipment (PPE) is one of the major causes of work-related accidents. In addition, Çelik et al [34] emphasize that the use of safety nets is an effective protective measure for high-rise construction, but there are still problems in testing and labeling safety nets in developing countries such as Turkey and Iran. Kazaz et al [35] further mention that occupational health and safety measures need to be initiated through academic studies and field work in view of the increasing number of work-related accidents.…”
Section: Safety Specific Examples From the Industrymentioning
confidence: 99%
“…The fact that it is a sector that includes works performed by different organizations and subcontractors, the existence of unskilled labour that is constantly moving, the working conditions vary according to the workplace. It is possible to list the factors such as the change in the workplace, the dispersed and wide working area, the height of the working environment, the natural climatic conditions, the low level of education of the employees [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%